Anodising as pre-treatment for structural bonding - Bjorgum, A.; Lapique, F.; Walmsley, J.; Redford, K.
Degradation of adhesive bonded aluminium profiles in various environments has been investigated in terms of the tensile strength of lap shear joints and wedge testing. Prior to adhesive bonding, the extrusions were pre-treated using various anodising processes. The results showed that anodising conditions, and thus structure and thickness of the anodised films, affect adhesion and durability of the adhesive joints. Tensile lap-shear testing of samples exposed in corrosive environments showed that hot AC anodising, using either sulphuric or phosphoric acid electrolytes, performed as well as standard PAA in spite of much shorter anodising times and no etching step prior to anodising. This was confirmed by wedge testing at high relative humidity. Wedge results, however, showed adhesive fracture of samples hot AC anodised in sulphuric acid, while cohesive fracture was found for samples anodised in phosphoric acid.
Keywords: EPOXY; ALUMINIUM AND ALLOYS; SURFACE TREATMENT; DURABILITY